PENGARUH PENAMBAHAN NANOZEOLIT ALAM DALAM PREPARASI NANOKOMPOSIT FOAM POLIURETAN TERHADAP SIFAT MEKANIK - Fransiskus Gultom; Hernawaty Hernawaty (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
The processing and characterization of polyurethane nanocomposite foam by adding Sarulla natural nanozeolit filler have been researched. The stages in the research of the processing of polyurethane nanocomposite foam were: 1) the preparation and purification of natural zeolit, 2) the processing of nanozeolit, 3) the processing of polyurethane nanocomposite foam using in situ process by mixing natural nanozeolit into the mix of polypropylene glycol and toluene diisocyanate. The result of the analysis of particle size analyzer showed that the Sarulla nanozeolit particle size was 95,8 nm. The variation of percentage ratio of nanozeolit as filler to polypropylene glycol and toluene diisocyanate was (0, 5, 10, 15, 20 and 25)%. The result of tensil test by using ASTM D 638 V standard showed that polyurethane foam with 20% wt filler would increase the elastic modulus to 36% (219,9 MPa).